SUSTAINABLE ARCHITECTURE RESEARCH TRENDS: A BIBLIOMETRIC ANALYSIS FOCUSING ON BUILDING FAÇADE DESIGN WITH THE INFLUENCE OF THERMAL COMFORT - Husodo, Mokhammad Khafidz; Fauzi, Muhammad Riyan; Hasan, Muhammad Ismail; Widiastuti, Ratih (Journal of Architecture&ENVIRONMENT, 2025)
Buildings account for a significant portion of global energy use, making facade design a critical component in efforts to achieve sustainable architecture. In tropical climates, challenges such as high solar radiation, temperature, and humidity increase the demand for innovative facade strategies that improve thermal comfort and energy efficiency. Proven strategies such as shading devices, roof overhangs, and natural ventilation have demonstrated effectiveness in reducing indoor heat gain and increasing occupant comfort. This study aims to analyze current research trends in sustainable architecture with a focus on building facade design and its impact on thermal comfort. Bibliometric analysis was carried out using Scopus-indexed publications from 2016 to 2025, with keywords related to building design, thermal comfort, and facade efficiency. VOSViewer software was used to map keyword networks, visualize publication trends, and identify dominant themes and research clusters. The analysis includes 51 relevant publications and reveals a growing interest in facade-related energy research over the last decade. The majority of research is focused on engineering, energy, and environmental science, with global contributions from China, the United States, and Italy. Keyword clustering identified three core research themes: architectural design strategies, building envelope technologies, and thermal comfort performance. Despite a growing body of research, this study highlights a gap in facade design research specifically adapted to tropical climates, where humidity and solar radiation issues require more context-sensitive solutions. These findings underscore the need for more localized and multidisciplinary research, as well as the integration of adaptive and intelligent façade systems. This research contributes to the knowledge base by identifying research patterns and gaps, offering a foundation for future investigations into facade innovations that support energy-efficient and thermally comfortable buildings in diverse climate contexts.